Microsoft Exchange server 2013 : mailbox and high availability - Redmond, Tony (Inside out (Redmond, Wash.), 2013)
With a focus on mailbox and high availability features, this book delivers the ultimate, in-depth reference to IT professionals planning and managing an Exchange Server 2013 deployment. Guided by Tony Redmond, a Microsoft MVP and award-winning author, you will: Understand major changes to Exchange Server architecture Get inside insights for planning your upgrade or deployment Examine the new web-based Exchange admin center (EAC) Take a deep dive into configuring mailboxes, distribution groups, and contacts; planning and managing the Managed Store; database availability groups; mailbox replication service; compliance, data leakage, and data loss prevention; site mailboxes; modern public folders.